2015
DOI: 10.1111/pan.12634
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of levobupivacaine associated with two different intermittent wound infusion regimens following surgical ductus ligation in preterm infants

Abstract: The two studied intermittent infusion regimens were associated with plasma levels below potentially toxic levels and were both associated with adequate postoperative pain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…17,18 Regional anaesthetic techniques are now used in children 2 and can be used even in extremely preterm infants. 19 However, unintentional overdosing, inadvertent intravascular administration, or excessive absorption of LAs from the injection site may cause serious side-effects (e.g. seizures and haemodynamic collapse).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Regional anaesthetic techniques are now used in children 2 and can be used even in extremely preterm infants. 19 However, unintentional overdosing, inadvertent intravascular administration, or excessive absorption of LAs from the injection site may cause serious side-effects (e.g. seizures and haemodynamic collapse).…”
Section: Discussionmentioning
confidence: 99%
“…6e8 In earlier studies, we have found acceptable plasma concentrations of LAs regarding the risk of LAST, combined with the lack of observed side-effects both in preterm and term newborn infants. 19 Even so, there are still unresolved safety issues especially in preterm infants. Defining the AAGP plasma concentrations also in the preterm population is of importance, as low concentrations will reduce plasma protein binding, thereby increasing the free and potentially toxic plasma concentration of LAs.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the levels of levobupivacaine in plasma remained below the toxic threshold. Furthermore, earlier studies have not reported high plasma ropivacaine concentrations with ropivacaine 2 mg·ml −1 in either children of different ages or adults . In the study of Beaussier and colleagues, ropivacaine 20 mg·h −1 was infused into adults for 48 h and both unbound and total fraction of ropivacaine decreased between 24 and 48 h, which suggested the absence of drug accumulation .…”
Section: Discussionmentioning
confidence: 95%
“…Anell-Olofsson reported plasma concentrations of levobupivacaine in the first 24 h of 0.0625% levobupivacaine wound infusion postneonatal thoracotomy. The median total levobupivacaine concentrations was 0.55 lgÁml À1 if infusion of levobupivacaine started 8 h postoperatively and 1.68 lgÁml À1 following a 0.2 mgÁkg À1 bolus and 2 mgÁkg À1 Áday À1 infusion (18). Krylborn reported unbound levobupivacaine plasma concentrations were stable and below 0.05 lgÁml À1 up to 72 h postoperatively using wound catheter infusions (19).…”
Section: Discussionmentioning
confidence: 99%